Illiberal Discourse in Romania: A “Golden” New Beginning? - Dragolea, Alina (2022)
While interest in illiberalism has increased in recent years, the study of the connections between anti-gender discourse and transnational dissemination is a more recent scholarly endeavour. Emerging feminist scholarship has helped to move beyond national cases of illiberalism to understand how the gendered nature of illiberalism is revealed through its ability to cross borders and, in recent years, to become a movement with a transnational character. This article examines the evolution of the political discourse on gender in Romania and proposes a three-stage framework leading from gender traditionalism to a more pronounced illiberal discourse. The article examines whether the recent rise of the political party Alliance for the Union of Romanians (Alianța pentru Unirea României, AUR) represents a new step towards an established political illiberal discourse in Romania. The official public addresses of AUR are analysed to show how the terminology and themes identified as cornerstones of illiberalism (e.g., anti-gender, traditional family, opposition to reproductive rights, education, and anti-LGBTQ) are incorporated into its rhetoric.